Synthesis and reactivity toward olefin exchange and oxidative addition of some platinum(0) olefin complexes with thioquinolines as spectator ligands. (17th June 2017) - Canovese, Luciano; Visentin, Fabiano; Scattolin, Thomas; Santo, Claudio; Bertolasi, Valerio
Graphical abstract: We have synthesized and characterized several platinum(0) complexes stabilized by thioquinoline and olefin ligands. We have kinetically studied the olefin-olefin, olefin-alkynes exchange and oxidative addition of alkyl halides to the synthesized species and resolved the solid state structure of a couple of diastereoisomers. Abstract: We have synthesized and fully characterized by NMR, IR and elemental analysis sixteen Pt(0) derivatives stabilized by four different thioquinoline spectator ligands and four different deactivated olefins. Moreover we have studied the reactivity and proposed a mechanism for olefin-olefin, olefin-alkyne exchange and oxidative addition of alkyl halides to this new class of Pt(0) derivatives based on detailed kinetic measurements. The kinetic study was carried out by NMR and UV–Vis techniques and in one case we have determined the activation parameters. Finally, we were able to resolve the solid state structure of a couple of diastereoisomers among the four possible isomers generated by the combination of two stereocenters.